2003
DOI: 10.1021/cm034399c
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Adsorption Properties for Thiophene of Nanostructured W2C on Ultrahigh-Surface-Area Carbon Materials

Abstract: Nanostructured tungsten carbides on ultrahigh-surface-area carbon (>3000 m2/g), a kind of novel carbon material with uniform pore distribution, have been prepared by carbothermal reduction, carbothermal hydrogen reduction, and metal-promoted carbothermal hydrogen reduction under mild conditions. The resulting carbides have been characterized by X-ray diffraction, transmission electron microscopy, temperature-programmed reduction−mass spectroscopy, and N2 physico-sorption. The adsorption properties of thiophene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 58 publications
3
54
0
1
Order By: Relevance
“…The preparation of tungsten carbide on activated carbon support is similar to that reported by Liang et al [18]. An aqueous solution of ammonium metatungstate containing desired W content was impregnated onto the activated carbon (provided by NORIT Company, with a specific area of 1280 m 2 /g) or alumina (home-made, with a specific area of 217 m 2 /g) support, followed by drying at 120°C overnight and calcination at 500°C in N 2 (for AC) or in air (for Al 2 …”
Section: Catalyst Preparationsupporting
confidence: 71%
See 1 more Smart Citation
“…The preparation of tungsten carbide on activated carbon support is similar to that reported by Liang et al [18]. An aqueous solution of ammonium metatungstate containing desired W content was impregnated onto the activated carbon (provided by NORIT Company, with a specific area of 1280 m 2 /g) or alumina (home-made, with a specific area of 217 m 2 /g) support, followed by drying at 120°C overnight and calcination at 500°C in N 2 (for AC) or in air (for Al 2 …”
Section: Catalyst Preparationsupporting
confidence: 71%
“…Recently, Vieira et al reported that carbon nanofibers with macroscopic shaping could act as an interesting support of iridium for hydrazine decomposition [15][16][17], but they did not report the methanation side effect. To the best of our knowledge, tungsten carbide supported on activated carbon has so far not been attempted for N 2 H 4 decomposition, although it could be prepared under relatively mild conditions via a carbothermal reduction or carbothermal hydrogen reduction process [18]. In the present work, we for the first time reported that the activated carbon supporting tungsten carbide (W 2 C/AC) exhibited excellent performance in the hydrazine decomposition, which was superior to the alumina supporting one (WC/ Al 2 O 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Evidently, the presence of nickel lowered the W 2 C formation temperature by approximately 100 K, possibly arising from nickel-promoted H 2 dissociation and thereby the reduction of the tungsten precursor. [20] Transmission electron microscopy (TEM; Figure S1 in the Supporting Information) and CO chemisorption ( Figure S2 in the Supporting Information) also confirmed the presence of nickelinduced agglomeration of W 2 C particles. This could be explained by the nickel-promoted methanation of the carbon support ( Figure S3 in the Supporting Information).…”
mentioning
confidence: 84%
“…W 2 C/AC and nickel-promoted W 2 C/AC catalysts were prepared by a carbothermal hydrogen reduction (CHR) method following our previous report [14] and the method of Liang et al [20] Characterization of the samples showed that the addition of nickel brought about remarkable changes in the evolution of the W 2 C phase as well as the particle size distribution. The XRD patterns of samples prepared at different CHR temperatures show that the phase composition was critically dependent on the CHR temperature (Figure 1).…”
mentioning
confidence: 99%
“…With a few notable exceptions, almost all of the published work on these materials has referred to the unsupported bulk compounds, and increasing the surface area (and hence the catalytic reactivity) has been a major objective. Some studies have used alumina [4], carbon [5] or mesoporous silica [6] supports to enhance the dispersion of the carbide or nitride phase.…”
Section: Introductionmentioning
confidence: 99%